A surprise cause of recurrent pneumonia in an infant - Thakur, Rashika; Sharma, Yash Pal; Sharma, Shruti (International Journal of Contemporary Pediatrics, 2025)
Foreign body (FB) ingestion is a common pediatric emergency seen among children between 6 months to 5 years. Most of the ingested FBs are accidentally taken and are passed in stools uneventfully, however they may lead to complications in some children. We present an infant with recurrent pneumonia attributed to gastroesophageal reflux due to a large Tik-Tak hair pin accidentally discovered on X-ray abdomen. The child symptomatically improved following endoscopic removal of the FB with complete resolution of respiratory symptoms and gastrointestinal reflux disease. Impacted FBs in fundus of stomach can irritate the mucosal lining, resulting in inflammation or increased acid secretions which may eventually lead to reflux of stomach contents into oesophagus (Gastro-oesophageal reflux). Aspiration of these reflux particles can cause recurrent aspiration pneumonia. After endoscopic removal of FB infant improved symptomatically and had no complains on follow up, which further proved that his symptoms were due to this large impacted FB. Thus, awareness among parents regarding ingested FBs and their complications is extremely important.